The role of corporate social responsibility in increasing company growth through micro waqf bank as a solution for economic resilience in the pandemic - Puji Harto; Warno Warno; Tarmizi Achmad (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - The purpose of this study was to determine the effect of corporate social responsibility (CSR) on increasing company growth through Micro Waqf Banks (a case study of Micro Waqf Bank customers during the covid 19 pandemic).Method - The data were analyzed through the stages of reduction, display, and heuristic data, that is concluding from various data and findings obtained by researchers both from secondary data and primary data.Result - Micro Waqf Banks provide loans with small margins so that cheap funding is needed, namely from government grants and CSR from companies, even from personal sources. But in practice, the institution has difficulty in the process of increasing the funding so that, in general, it still comes from government grants. From the results of the study, 50% of business customers increased so Micro Waqf Banks could affect the economic improvement of community members, especially Micro Waqf Bank customers.Implication - MSMEs have increased from 10-40% so that it directly affects the economy of Micro Waqf Bank customers. This also indirectly affects the community's economy because of the associated economic cycle even during the COVID-19 pandemic.Originality - This research is the first research using CSR and Micro Waqf Banks to increase company growth directly and to the country's economic growth indirectly.